(untitled) (Development Service Industry Management, 2025)
In the modern context of educational reform and growing competition among educational institutions, improving management efficiency has become one of the key factors in their development. Educational institutions strive to strengthen their reputational capital and ensure long-term competitiveness, which, in turn, increases the demands on managers and academic staff. A modern educational leader is expected not only to possess managerial competencies but also to demonstrate the ability for self-development, rational allocation of time, resources, and personal potential. In this regard, self-management acquires particular significance as a system of self-governance in professional activity. The purpose of this study is to determine the essence, structure, and specific features of implementing self-management by the head of an educational institution under the conditions of contemporary challenges and educational transformations. The article analyzes various scientific approaches to understanding the concept of “self-management,” presented in the works of Ukrainian and international researchers. The research findings show that the effectiveness of a leader’s managerial activity directly depends on the level of self-management skills, among which the key ones are planning, goal setting, self-control, self-motivation, self-analysis, and personal responsibility. Self-management is considered an integrated system that combines planning, priority setting, task performance control, self-discipline, and personal development. This system ensures the rational use of time, resources, and emotional potential and contributes to achieving the strategic and tactical goals of an educational institution. The application of effective self-management models enhances managerial productivity, strengthens stress resilience, develops adaptability to change, and creates favorable conditions for sustainable institutional development. In the context of digital transformation, increasing autonomy of educational institutions, and growing quality demands, mastery of self-management tools becomes a necessary condition for professional success. Self-management is an integral component of an educational leader’s managerial competence, determining their ability to effectively organize personal activities, make informed decisions, use resources efficiently, and maintain productive teamwork. Developed self-management skills ensure flexibility, adaptability, and the sustainable development of educational institutions in the constantly changing educational environment.